Efektivitas Karyawan WFH, WFO dan Hybrid Pasca PPKM Pandemi Covid-19 Metode Analitycal Hierarchy Process - Putra Edi Mujahid; Jansen Yudistira S Meliala; Albert Pratama Sembiring (STMIK Budi Darma, 2023)
The purpose of this study was to see the effectiveness of employees from the work from home (WFH), work from office (WFO) and WFH-WFO (hybrid) methods after the Covid-19 pandemic PPKM (Implementation of Restrictions on Community Activities) was revoked by the government in December 2022 This research is a descriptive research using a survey method using a purposive sampling technique, in which the authors distribute questionnaires to respondents from 100 employees to ask for their opinion. Respondents are employees of the telecommunications sector in one of the telecommunications companies in the city of Medan. The survey period was conducted for one month in January 2023. The Covid-19 pandemic has changed many patterns of human life, one of which is the work from home, work from office, and hybrid work systems. With the announcement of the end of the Covid-19 PPKM in Indonesia, researchers wanted to find out how much influence the effectiveness of employees who had previously been accustomed to working patterns during the Covid-19 pandemic, this is what is discussed in this article. There are four criteria in determining the effectiveness of employees after the Covid-19 pandemic PPKM. The first criterion is productivity, then flexibility, then communication and the last is administration. From the results of the data processing, some data was generated showing that employees preferred the WFH work system, namely with the highest ranking value of 0.4734, which was still carried out after the PPKM information was revoked by the government, because with this working method employees are more flexible, can work at any time and feel more protected and considered comfortable to complete the job.